A treatment method for the gnatic form of the mesial occlusion - Grigorenko, Ya.M.; Grigorenko, A.Ya.; Тоrmakhov, N.N.; Shpak, D.Yu.; Flis, P. S. (Reports of the National Academy of Sciences of Ukraine, 2014)
By the methods of biomechanics, a mathematical model of the work of a facepiece is built, and its supporting reactions are determined. Supporting reactions are got for various slope angles of the force vector of a rubber pull applied to the supramaxilla.